Jimi Ventures & Co.: C.A.D. class & services / Awang Mohamed Hazim Norajiki ... [et al.] - Norajiki, Awang Mohamed Hazim; Muntigas, Danester Denson; Taring, Franky Lirang; JP Sitaim, Jordan; Hashim, Muhammad Hazmi; Wan Chik, Muhammad Zulfawza (2019)
Jimi Ventures & Co. was founded in 2016 and the company offers C.A.D. Class and services where you can easily have you work done flawlessly. Our store will give priority activities in producing quality design for our clientele. Our principal office is located at Kompleks Pusat Bandar Pasir Gudang, Johor. We choose this place because it is the centre of business hence there is a huge crowd that might be seeking our services. Jimi Ventures & Co. is trying to provide C.A.D. services and certifications towards up and coming designers, freelancers and small company rather than focusing on major companies. Our main quest is to produce quality design and quality designers. We believe that the company will be able to stay strong in the scene as even now the C.A.D. is widely used. Although the services that we provide are widely available, we believe that our company will be able to compete in completing the task with quality and in the time frame given.